Sal Regeneration do Nova in B3 Sal - Warren, D. W. (Indian Forester, 1941)
The premonsoon rainfall of the United Provinces forest is poor compared with Singhbhum, Bihar, and would appear to have diminished during the past century due probably to heavy fellinigs outside the Reserves. It may perhaps account in part for sal regeneration difficulties of the Bhabar Tract. Contour trenching in the drier forest types, by improving the forest growth, would bring about a climatic improvement.